Dynamic aspects of vacuolar and cytosolic amino acid pools of Saccharomyces cerevisiae. - Kitamoto, K (1988)
By using the Cu2+ method (Y. Ohsumi, K. Kitamoto, and Y. Anraku, J. Bacteriol. 170:2676-2682, 1988) for differential extraction of the vacuolar and cytosolic amino acid pools from yeast cells, the amino acid compositions of the two pools extracted from Saccharomyces cerevisiae cells, grown in synthetic medium supplemented with various amino acids, were determined. Histidine and lysine in the medium expanded the vacuolar pool extremely. Glutamate also accumulated in the cells, but mainly in the cytosol. The composition of amino acids in the cytosolic pool was fairly constant, in contrast to that in the vacuolar pool. Cells grown in synthetic medium supplemented with 10 mM arginine accumulated arginine in the vacuoles at a concentration of about 430 mM. This large arginine pool was metabolically active and was effectively utilized during nitrogen starvation. Arginine efflux from the vacuoles was coupled with K+ influx, with an arginine/K+ exchange ratio of 1, as judged by the initial rate. The vacuolar arginine pool was exchangeable with lysine added to the medium and was decreased by treatment of the cells with the mating pheromone, alpha-factor.